Impact of educational intervention on awareness of pharmacovigilance among medical undergraduates in Karnataka, India: a cross-sectional study - Shivaraju, Padmanabha Thiruganahalli; Gangadhar, Manu; Manchukonda, Ravi Shankar; Thippeswamy, Chandrakantha; Krishnegowda, Neha (International Journal of Basic & Clinical Pharmacology, 2016)
Background: India being a part of national pharmacovigilance program (NPP), its contribution to UMC (Uppsala monitoring centre) is very little and pharmacovigilance program of India (PvPI) is still in its infancy. Lack of vibrant reporting culture necessitates bringing the awareness and importance of it. Objective of this study was to assess the level of knowledge, awareness, and the method of application of pharmacovigilance (PV) and to evaluate the impact of an educational intervention among second year medical students for improving awareness of pharmacovigilance. Methods: This was a cross-sectional questionnaire based study conducted among 146 students in a tertiary care teaching hospital in B.G. Nagara, Mandya, Karnataka, India. Purpose of the study was explained to all the participants. Pretest questionnaires were distributed and filled questionnaires were collected following the educational intervention through continued medical education (CME), same questionnaire was given as post-test questionnaire. Both the test results were analysed to know the educational impact. Results: Out of 146, a total 130 medical students were involved in pre and post-test questionnaire. The overall response rates between pre and post intervention had improved in majority of the medical undergraduates which brings out the effectiveness of intervention for improving the reporting system. Conclusions: Educational intervention was more effective in improving student’s knowledge, awareness and applications of pharmacovigilance. Early sensitization through educational interventions in II phase of MBBS itself enhances the reporting frequency in future through their active participation & emphasizing the need to design the suitable strategies to develop vibrant as well as voluntary reporting culture.